Surface sites on Pt-CeO2 mixed oxide catalysts probed by CO adsorption: a synchrotron radiation photoelectron spectroscopy study - Neitzel, Armin; Lykhach, Yaroslava; Skala, Tomas; Tsud, Nataliya; Vorokhta, Mykhailo; Mazur, Daniel; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Physical Chemistry Chemical Physics, 2014)
By means of synchrotron radiation photoemission spectroscopy, we have investigated Pt-CeO2 mixed oxide films prepared on CeO2(111)/Cu(111). Using CO molecules as a probe, we associate the corresponding surface species with specific surface sites. This allows us to identify the changes in the composition and morphology of Pt-CeO2 mixed oxide films caused by annealing in an ultrahigh vacuum. Specifically, two peaks in C 1s spectra at 289.4 and 291.2 eV, associated with tridentate and bidentate carbonate species, are formed on the nanostructured stoichiometric CeO2 film. The peak at 290.5-291.0 eV in the C 1s spectra indicates the onset of restructuring, i.e. coarsening, of the Pt-CeO2 film. This peak is associated with a carbonate species formed near an oxygen vacancy. The onset of cerium oxide reduction is indicated by the peak at 287.8-288.0 eV associated with carbonite species formed near Ce3+ cations. The development of surface species on the Pt-CeO2 mixed oxides suggests that restructuring of the films occurs above 300 K irrespective of Pt loadings. We do not find any adsorbed CO species associated with Pt4+ or Pt2+. The onset of Pt2+ reduction is indicated by the peak at 286.9 eV in the C 1s spectra due to CO adsorption on metallic Pt particles. The thermal stability of Pt2+ in Pt-CeO2 mixed oxide depends on Pt loading. We find excellent stability of Pt2+ for 12% Pt content in the CeO2 film, whereas at a Pt concentration of 25% in the CeO2 film, a large fraction of the Pt2+ is converted into metallic Pt particles above 300 K.